Export diversification in emerging economies - Karahan, Hatice (Springer International Publishing Ag, 2017)
The positive impact of export diversification on countries' economic growth is widely recognized in literature. Moreover, there has been a growing consensus lately on the role of diversification as a protection tool against crises and shocks. In other words, countries with higher export concentrations are thought to be exposed to more susceptibilities and vice versa. Hence, for most developing countries, for which exports performance are vital, understanding the so-called association matters. This study aims at providing evidence for certain emerging economies in that respect and starts with illustrating the performance of the BRICS and MINT economies in terms of product/sector and market diversification in the 2000s. The chapter then investigates the relationship between export concentration and trade collapse for the 2008-2009 global crisis. Conclusions derived by the study show resemblance to certain findings in literature and address to a positive relationship between the level of product concentration and the severity of trade collapse in case of a crisis. Basic calculations on the market diversification, however, do not imply a meaningful relationship for the period in question.
WOS: 000409545700023
Keywords: Emerging Economies; Diversification; Economic Growth